Restorative Justice Bagi Anak Pelaku Tindak Pidana Perkosaan Anak Perspektif Hukum Islam dan Hukum Positif - Ridho Rokamah (Justicia Islamica, 2013)
The high number of cases of sexual violence against children in the UPPA of the Polres and the Women's and Children's Protection Committee of Ponorogo District has recently put law enforcers (judges, prosecutors, and police) in a difficult position. The officialsThey prefer to provide a policy not to process the case, especially if the victim's family and the perpetrator want to make peace after the victim becomes pregnant. If the facts and evidence require punishment, then lenient charges are the preferred alternative. The reason is that children are victims of the environment (family/friends) who need education. This policy of law enforcement officials, especially the Polres, is called restorative justice because there is an element of deliberation or agreement for the sake of justice from the victim and the perpetrator. In the Islamic perspective, children who are still not legally accountable for their actions (not yet mukallaf) are not subject to punishment as adults. In Islam, there is a limitation that criminal law can be applied to children until they become mukallaf, if they have not reached that age, the law cannot be applied. As in positive law, the law can be applied to anyone without age limit. It's just that for children criminal offenders must be treated specifically.